Study on Knowledge and Practices of Water, Sanitation and Hygiene among Secondary School Students - Shrestha, Marina Vaidya; Manandhar, Naresh; Joshi, Sunil Kumar (Journal of College of Medical Sciences-Nepal, 2018)
Background: Provision of adequate water supply, sanitation, hygiene and waste management in schools has a number of positive effects. The study focuses on children because disease related to water; sanitation and hygiene are the leading cause of mortality and morbidity among children. Materials and Methods: This cross-sectional study comprised of 220 students. Participants involved were Government school students of grades 9-10 in Sindhupalchowk and Bhaktapur. Data consisted of hygiene and hand washing practices, knowledge about sanitation and personal hygiene characteristics. Results: This study revealed that knowledge regarding water borne disease was high among Urban school students 86.5% but knowledge regarding transmission route seemed inadequate in both urban and rural students (35% and 16% respectively). The practice on hand washing was found high (94.4%).There was significant difference in the knowledge of students regarding WASH in urban and rural settings of the school (P value<0.001). Treated water facility and hand washing facilities with water was found lacking in rural schools. Schools from the urban area had proper hand washing facilities, but there was not any soap available in both the areas. Conclusions: The knowledge and practice of Water, Sanitation and Hygiene (WASH) among secondary school students is still poor. The knowledge of WASH in secondary school students when compared to the rural areas, urban areas had better on the basis of knowledge score. Keywords: hygiene; knowledge; practice; water; sanitation.